Spouted bed drying on inert particles: Evaluation of particle size distribution of recovered, accumulated and elutriated powders. Issue 13 (1st September 2020) - Barros, João P. A. A.; Ferreira, Maria C.; Freire, José T.
Abstract: The performance of a spouted bed in drying a liquid suspension of calcium carbonate was evaluated through the analysis of particle size distributions of the products recovered from different parts of the dryer. The effects of the air temperature and paste feed flow rate on the particle size distributions and mean sizes were investigated. Depending on the drying conditions, solid mass fractions from 11 to 53% were collected at the cyclone underflow, from 2 to 8% were retained in the filter and from 23 to 34% accumulated in the drying vessel. The results provide compelling evidence that dried powder is highly heterogeneous in size. The sizes of particle's clusters accumulated in the dryer column and collected in the cyclone underflow were enlarged by increasing the paste feed flow rate. The mean sizes of accumulated material varied from 3.7 to 47.1 μm. The sizes of powder elutriated in the cyclone overflow and collected in the cyclone underflow ranged respectively from 0.95 to 1.4 μm, and from 2.6 to 7.0 μm.